Drawn from courtly India : the Conley Harris and Howard Truelove Collection - Cameron, Ainsley M. (Ainsley MacDougall), 1979-; Mason, Darielle; Philadelphia Museum of Art (Philadelphia : Philadelphia Museum of Art in association with Yale University Press, 2015)
This publication presents the first in-depth survey of the Conley Harris and Howard Truelove Collection of Indian drawings, which was recently acquired by the Philadelphia Museum of Art. This exceptional collection, which has never previously been published, consists of 65 works on paper created between the 16th and 19th centuries. The Harris-Truelove Collection is uniquely and tightly focused on works from the royal courts of North India, and the majority of these drawings served as preparatory material for the opaque watercolor illustrations that have been widely collected and studied. This catalogue celebrates the assured line of the Indian draftsman and recognizes these drawings as accomplished works of art in their own right. The text details the process and technique involved in their production, and explores what can be revealed by the artist's hand. This in-depth look at drawings also contextualizes the role of art production in court culture, and reveals the intricacies of artistic workshop practice.0Exhibition: Philadelphia Museum of Art, USA (28.11.-27.3.2016).
Published on the occasion of the exhibition "Drawn from Courtly India: The Conley Harris and Howard Truelove Collection," Philadelphia Museum of Art, December 6, 2015 - March 27, 2016.
Includes bibliographical references (pages 130-131).
Keywords: Harris, Conley, -- 1943- -- Art collections -- Exhibitions; Truelove, Howard, -- 1946-2012 -- Art collections -- Exhibitions; Conley Harris and Howard Truelove Collection (Philadelphia, Pa.); Philadelphia Museum of Art; Drawing, Indic -- Exhibitions; Drawing, Indic -- Pennsylvania -- Philadelphia -- Exhibitions; India -- In art -- Exhibitions; Exhibition catalogs